HIF-1α/BNIP3L induced cognitive deficits in a mouse model of sepsis-associated encephalopathy - Zhao, Lina; Song, Yu; Zhang, Ying; Liu, Haiying; Shen, Yuehao; Fan, Yan; Li, Yun; Xie, Keliang (Frontiers in Immunology, 2022)
Abstract Objective: Sepsis Associated Encephalopathy (SAE) is a common complication in critically ill patients and perioperative period, but its pathogenesis is still unclear. This study aimed to explore the effect of the HIF-1α (hypoxia-inducible factor-1α)/BNIP3L (Bcl-2/adenovirus E1B 19-kDa interaction protein) signaling pathway on SAE. Methods: C57BL/6J male mice were divided into four groups, using a random number table method: control group, sham group, sepsis group, sepsis+HIF-1α activity inhibitor (echinomycin) group. Sepsis was induced by cecal ligation and puncture (CLP). At 24 h after surgery, brain tissue was sampled. HE was staining to observe changes in the hippocampus structure. Fluoroscopy observes changes in mitochondrial structure. Western blot, QT-PCR, and immunofluorescence were used to assess the amount of expression of HIF-1α and BNIP3L in the hippocampus and mitochondrion of hippocampus neurons. Observation of neuronal apoptosis by TUNEL staining. Seven days after surgery, mice were tested in a Morris water maze test to assess cognitive function after CLP . Results: Our results show that CLP-induced hippocampus-dependent cognitive deficits were accompanied with increased HIF 1a and decreased BNIP3L, increased protein levels of TNF-α, IL-6, and IL-β, and damage to mitochondrial structures and neuronal apoptosis in the hippocampus. In addition, administration of echinomycin rescues cognitive deficits, ameliorates HIF-1α and BNIP3L-mediated neuronal pyroptosis and damaged mitochondrial structures, and decreases the expression of TNF-α and IL-6 in the hippocampus. Conclusions: HIF-1α and the BNIP3L promote mitochondrial damage, and neuronal apoptosis and the expression of inflammatory factors may be the mechanism of SAE in critically ill patients and perioperative period